Analisis Hukum Kontrak Jual Beli - Khalilul Anna Billahi Robbi; Ainurrahman Ardhiyanto (JOURNAL SAINS STUDENT RESEARCH, 2023)
Legal Analysis of Sales and Purchase Contracts is an in-depth study of the legal aspects governing sales and purchase agreements within the realm of civil law. In this context, the research investigates various facets, including the formation of contracts, rights and obligations of the parties involved, as well as the legal implications arising from sales and purchase transactions. Employing a positive legal approach, the study reviews applicable legal norms, case precedents, and relevant regulations to comprehend the fundamental concepts and principles that govern sales and purchase contracts. The research also involves an analysis of changes and developments in regulations that may impact the implementation of sales and purchase contracts in the contemporary era. Additionally, the study explores legal issues that may arise, such as contract breaches, ethical considerations, and consumer protection within the context of buying and selling. The outcomes of this analysis are anticipated to provide profound insights into the legal framework regulating sales and purchase contracts, contributing to the development of civil law and sustainable business practices in society.